Insulin Resistance in HIV-Patients: Causes and Consequences - Pedro, Marcelo N.; Rocha, Guilherme Z.; Guadagnini, Dioze; Santos, Andrey; Magro, Daniela O.; Assalin, Heloisa B.; Oliveira, Alexandre G.; Pedro, Rogerio de Jesus; Saad, Mario J. A. (Frontiers in Endocrinology, 2018)
Abstract Here we review how immune activation and insulin resistance contribute to the metabolic alterations observed in HIV-infected patients, and how these alterations increase the risk of developing CVD. The introduction and evolution of antiretroviral drugs over the past 25 years has completely changed the clinical prognosis of HIV-infected patients. The deaths of these individuals are now related to atherosclerotic CVDs, rather than from the viral infection itself. However, HIV infection, cART and intestinal microbiota are associated with immune activation and insulin resistance, which can lead to the development of a variety of diseases and disorders, especially with regards to CVDs. The increase in LPS and proinflammatory cytokines circulating levels and intracellular mechanisms activate serine kinases, resulting in insulin receptor substrate-1 (IRS-1) serine phosphorylation and consequently a down regulation in insulin signaling. While lifestyle modifications and pharmaceutical interventions can be employed to treat these altered metabolic functions, the mechanisms involved in the development of these chronic complications remain largely unresolved. The elucidation and understanding of these mechanisms will give rise to new classes of drugs that will further improve the quality of life of HIV-infected patients, over the age of 50.